Making the case for universal school-based mental health screening. Issue 1 (2nd January 2016) - Humphrey, Neil; Wigelsworth, Michael
Abstract : Mental health difficulties affect 1 in 10 children and adolescents, and up to half of adult cases begin during the school years. The individual and societal impacts of such difficulties are huge, and include poorer quality of life, lost economic productivity, destabilisation of communities, and high rates of health, education and social care service utilisation. Using early intervention and prevention in schools as a central component of a co-ordinated response to this emergent public health crisis makes good sense. Schools play a central role in the lives of children and their families, and their reach is unparalleled. It has been argued that truly comprehensive and effective mental health promotion in schools requires a universal screening component, but this is a controversial proposition. In this article we explore some of the opportunities and challenges posed by such a system. In doing so, we critically assess international literature on social validity (e.g. acceptability, feasibility and utility), definition and conceptualisation (e.g. what do we mean by 'mental health' and related terms?), design and implementation (e.g. planning, tool selection, linking to referral and intervention systems), psychometric considerations (e.g. are available instruments reliable and valid?), diversity (e.g. taking into account cultural variation) and costs and benefits (e.g. are the human, financial and material costs of universal screening justified by the improvements in provision and outcomes they bring?). We conclude by presenting a vision for a school-based system that takes into account these important factors.